Pengembangan Sumber Daya Manusia dan Kepuasan Kerja terhadap Kinerja Karyawan PT. Megah Surya Pertiwi - Dailangi, Christi N.; Manoppo, Wilfried S.; Rumawas, Wehelmina (Productivity, 2020)
Performance is a measure for the success or failure of a company. There are many ways to improve an employee’s performance. This study aims to determine the effect of human resource development and job satisfaction on employee performance. Data collected through a questionnaire to 61 respondents, then analyzed using structural equation modeling (SEM) with partial least square approach. The results showed that the development effect. Human resources have a significant effect on employee performance. Source development human power has a significant effect on job satisfaction. Job satisfaction has an effect significant to employee performance. And there is no significant influence between. DevelopmentÂ human resources on employee performance mediated from job satisfaction. Based on this research, the company must carry out human resource development activities in order to increase knowledge and skills in order to create job satisfaction that becomes feedback that will affect the performance of employees of PT Mega Surya Pertiwi.